Manufacturing method of negative electrode of lithium battery
By forming a fluorine-containing protective film on the negative electrode of the lithium battery through electroplating process, the short circuit and thermal runaway caused by lithium dendrites are solved, and the stability and cycle life of the lithium battery are improved.
Patent Information
- Application Number
- CN202311363853.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2023-09-18
- Filing Date
- 2023-10-20
- Publication Date
- 2025-03-18
AI Technical Summary
When pure lithium metal is used as the negative electrode of lithium battery, lithium dendrites are prone to occur, resulting in short circuits and thermal runaway, reducing the stability and cycle life of lithium batteries.
The lithium deposition layer is formed on the copper foil by electroplating process, and an electrolyte containing organic solvents and fluorine-containing lithium salt is designed to form a fluorine-containing protective film to reduce the formation of lithium dendrites.
Effectively reduce the generation of lithium dendrites, reduce the chance of problems such as short circuit and thermal runaway, and improve the stability and cycle life of lithium batteries.
Smart Images

Figure CN119650600A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for manufacturing a negative electrode of a lithium battery. Background Art
[0002] Lithium batteries use lithium metal as the negative electrode and have a high theoretical capacity (e.g. 2047 mAh / cm 3 Up to 3860mAh / cm 3 Its advantages over the standard hydrogen electrode (SHE) include light weight and small ion radius, and it is considered to be very suitable for the development of high energy density batteries. However, it still has problems to be overcome.
[0003] For example, when pure lithium metal is used as the negative electrode, lithium dendrites are prone to occur during charging and discharging. As the battery operates for a longer time, they may pierce the isolation membrane and come into contact with the positive electrode, causing problems such as short circuit and thermal runaway, which will reduce the stability and cycle life of the lithium battery. Summary of the invention
[0004] The present invention provides a method for manufacturing a lithium battery negative electrode. The manufactured lithium battery negative electrode can effectively improve the stability and cycle life of the assembled lithium battery.
[0005] A method for manufacturing a negative electrode of a lithium battery of the present invention comprises providing a copper foil; and performing an electroplating process to form a lithium deposition layer on the copper foil. The electrolyte used in the electroplating process comprises an organic solvent and a fluorine-containing lithium salt, wherein the organic solvent comprises an ester solvent, an ether solvent, an alcohol solvent or a combination thereof, and the fluorine-containing lithium salt comprises lithium hexafluorophosphate (LiPF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium trifluoromethanesulfonate (LiTF), lithium difluoro(oxalato)borate (LiDFOB), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI) or a combination thereof.
[0006] In one embodiment of the present invention, the electrolyte is composed of lithium salt and ester or ether solvents or a mixture of ester and ether. Preferably, the electrolyte at least includes ester solvent and the volume ratio thereof accounts for more than 50%.
[0007] In one embodiment of the present invention, the usage ratio of the fluorine-containing lithium salt in the electrolyte is between 0.1 mol / L(M) and 5 mol / L(M).
[0008] In one embodiment of the present invention, the current density of the electroplating process is between 1 mA / cm 2 Up to 5mA / cm 2 between.
[0009] In one embodiment of the present invention, the thickness of the lithium deposition layer is between 1 micrometer and 20 micrometers.
[0010] In one embodiment of the present invention, the electrolyte further includes an additive, and the additive includes lithium nitrate (LiNO 3 ).
[0011] In one embodiment of the present invention, the usage ratio of the above-mentioned additive in the electrolyte is between 1 wt % and 10 wt %.
[0012] In one embodiment of the present invention, the organic solvent is selected from a combination of an ester solvent and an ether solvent.
[0013] In one embodiment of the present invention, the volume ratio of the ester solvent to the ether solvent is between 3:1 and 1:1.
[0014] In one embodiment of the present invention, the surface of the lithium deposition layer comprises a fluorine-containing compound.
[0015] Based on the above, the manufacturing method of the lithium battery negative electrode of the present invention is to form a copper-lithium composite structure through an electroplating process, and through the electrolyte design of the electroplating process, a fluorine-containing protective film can be formed on its surface. In this way, the generation of lithium dendrites can be effectively reduced during the charging and discharging of the lithium battery, and the probability of problems such as short circuit and thermal runaway can be reduced. That is, the lithium battery negative electrode manufactured by the method of the present invention can effectively improve the stability and cycle life of the assembled lithium battery.
[0016] In order to make the above features and advantages of the present invention more clearly understood, embodiments are given below and described in detail with reference to the accompanying drawings. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 The flowchart is a method for manufacturing a negative electrode of a lithium battery according to an embodiment of the present invention.
[0018] Figure 2 Schematic diagram of the structure of a negative electrode of a lithium battery according to an embodiment of the present invention.
[0019] Figure 3 , Figure 4 , Figure 5 , Figure 6 , Figure 7 , Figure 8 , Fig. 9 , Fig.10It is a SEM schematic diagram of Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Comparative Example 1 and Comparative Example 2 of the present invention.
[0020] Fig.11 , Fig.12 , Fig.13 , Fig.14 , Fig.15 , Fig.16 , Fig.17 , Fig.18 It is a schematic diagram of the change of surface capacitance under different current densities according to Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Comparative Example 1 and Comparative Example 2 of the present invention. DETAILED DESCRIPTION
[0021] In the following detailed description, for the purpose of illustration and not limitation, exemplary embodiments that disclose specific details are described to provide a thorough understanding of the various principles of the present invention. However, it will be apparent to one of ordinary skill in the art that, with the benefit of this disclosure, the present invention may be practiced in other embodiments that depart from the specific details disclosed herein. In addition, descriptions of well-known devices, methods, materials, and other specific details may be omitted to avoid obscuring the description of the various principles of the present invention.
[0022] In this article, the range expressed by "a value to another value" is a summary expression method to avoid listing all the values in the range one by one in the specification. Therefore, the description of a specific numerical range covers any value in the numerical range and a smaller numerical range defined by any value in the numerical range, just as the arbitrary value and the smaller numerical range are written in the description text of the specification.
[0023] Unless otherwise specified, the term "between" used in this specification to define a numerical range is intended to cover a range equal to the endpoint value and between the endpoint values. For example, a size range is between a first value and a second value, which means that the size range can cover the first value, the second value and any value between the first value and the second value.
[0024] In this document, non-limiting terms (such as may, could, for example, or other similar terms) mean optional or optional implementation, inclusion, addition, or presence.
[0025] Unless otherwise defined, all terms (including technical and scientific terms) used herein have the same meaning as those commonly understood or generally understood in the technical field to which the present invention belongs. It will also be understood that terms (such as those defined in commonly used dictionaries) should be interpreted as having a meaning consistent with their meaning in the relevant technical context and should not be interpreted in an idealized or overly formal sense unless explicitly defined as such herein.
[0026] Figure 1 The flowchart is a method for manufacturing a negative electrode of a lithium battery according to an embodiment of the present invention. Figure 2 is a schematic diagram of the structure of a negative electrode of a lithium battery according to an embodiment of the present invention. Figure 1 and Figure 2 The manufacturing method of the lithium battery negative electrode 100 of this embodiment may include at least the following steps. Figure 3 , Figure 4 , Figure 5 , Figure 6 , Figure 7 , Figure 8 , Fig. 9 , Fig.10 It is a SEM schematic diagram of Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Comparative Example 1 and Comparative Example 2 of the present invention. Fig.11 , Fig.12 , Fig.13 , Fig.14 , Fig.15 , Fig.16 , Fig.17 , Fig.18 It is a schematic diagram of the change of surface capacitance under different current densities according to Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, Comparative Example 1 and Comparative Example 2 of the present invention.
[0027] First, a copper foil 110 is provided (step S100), wherein the thickness 110T of the copper foil 110 is, for example, between 5 micrometers (um) and 10 micrometers, but the present invention is not limited thereto. Then, an electroplating process is performed to form a lithium deposition layer 120 on the copper foil 110, wherein the electrolyte used in the electroplating process includes an organic solvent and a fluorine-containing lithium salt (step S200).
[0028] Furthermore, the organic solvent includes an ester solvent, an ether solvent, an alcohol solvent or a combination thereof (in some embodiments, the electrolyte may include at least one or more organic solvents, such as an ester or ether solvent or a mixture of esters and ethers, and the electrolyte preferably includes at least an ester solvent), and the fluorine-containing lithium salt includes lithium hexafluorophosphate, lithium bis(trifluoromethylsulfonyl)imide, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl)imide or a combination thereof, wherein the fluorine-containing lithium salt can be used as an electrolytic solute to stabilize the negative electrode 100 of the lithium battery.
[0029] Accordingly, the manufacturing method of the lithium battery negative electrode of this embodiment is to form a copper-lithium composite structure (such as Figure 2The stacked copper foil 110 and the lithium deposition layer 120 are shown in FIG. 1 , and a fluorine-containing protective film can be formed on the surface thereof by designing the electrolyte of the electroplating process. In this way, the generation of lithium dendrites can be effectively reduced during the charging and discharging of the lithium battery, and the probability of problems such as short circuit and thermal runaway can be reduced. That is, the lithium battery negative electrode 100 manufactured by the manufacturing method of this embodiment can effectively improve the stability and cycle life of the assembled lithium battery. Here, the lithium battery can be a lithium secondary battery, a lithium metal solid-state battery, or the like.
[0030] In some embodiments, the fluorine-containing protective film refers to the surface of the lithium deposition layer 120 (eg Figure 2 The top surface in the electrolyte) includes a fluorine-containing compound (generated along with the electroplating process), so the lithium deposition layer 120 is not a pure lithium metal layer, and the type of the fluorine-containing compound can depend on the type of fluorine-containing lithium salt actually used in the electrolyte.
[0031] In some embodiments, the fluorine-containing protective film can be regarded as a solid electrolyte interface layer (Solid Electrolyte Interface, SEI) with a higher lithium content. The solid electrolyte interface layer designed to be formed in the lithium electroplating process on the copper foil using the electrolyte of this embodiment has the characteristics of uniformity and stability. Therefore, when assembled into a lithium battery, the formation of lithium dendrites can be suppressed and the battery has a high coulombic efficiency (CE), for example, a coulombic efficiency greater than 90%, but the present invention is not limited to this.
[0032] In some embodiments, the thickness 120T of the lithium deposition layer 120 formed by the manufacturing method of the lithium battery negative electrode of this embodiment is, for example, at least less than 30 microns, for example, can be between 1 micron and 20 microns (for example, 1 micron, 3 microns, 5 microns, 8 microns, 12 microns, 15 microns, 20 microns or any value between 1 micron and 20 microns), that is, it can operate well during the charge and discharge cycle process. Therefore, compared with the thickness of the lithium metal layer formed by the current technology (such as by cold rolling process) (which can even reach 300 microns), the thickness 120T of the lithium deposition layer 120 can be significantly reduced, so that the lithium battery has more advantages in cost and energy density, but the present invention is not limited to this.
[0033] In some embodiments, the thickness 110T of the copper foil 110 is 6 micrometers, and the thickness 120T of the lithium deposition layer 120 is 5 micrometers, so as to achieve better effects, but the present invention is not limited thereto.
[0034] In some embodiments, the ratio of the fluorine-containing lithium salt in the electrolyte is between 0.1 mol / L (M) and 5 mol / L (M). In this way, the current density of the electroplating process can be at least greater than 1 mA / cm 2 , for example, between 1mA / cm 2 Up to 5mA / cm 2 Compared with the low current density commonly used in current technology (such as 0.1mA / cm 2 Up to 0.5mA / cm 2 ), the present invention can reduce the electroplating time and improve the yield, while reducing the formation of lithium dendrites and achieving a higher coulombic efficiency, thereby facilitating commercial mass production, but the present invention is not limited thereto.
[0035] In some embodiments, the organic solvent includes ethylene carbonate (EC), diethyl carbonate (DEC), fluoroethylene carbonate (FEC), dimethyl carbonate (DMC), propylene carbonate (PC), ethylene glycol dimethyl ether (1,2-dimethoxyethane, DME), acetaldehyde diethyl acetal (1,1-diethoxyethane, DEE), 1,3-dioxolane (DOL) or a combination thereof, but the present invention is not limited thereto, and the organic solvent may also be any other suitable ester solvent, ether solvent, or alcohol solvent.
[0036] In some embodiments, the electrolyte further includes an additive, and the additive includes lithium nitrate (LiNO3), so that its surface morphology has a better state, such as improving the surface flatness in the electroplating system of the nucleation reaction, thereby reducing the probability of uneven nucleation and uneven surface, and further reducing the possibility of forming lithium dendrites, but the present invention is not limited to this, and the additive can be optionally configured, that is, the additive can also be omitted in the electrolyte. Here, the proportion of the additive in the electrolyte is, for example, between 1wt% and 10wt%.
[0037] In some embodiments, the electrolyte is composed of an organic solvent, a fluorine-containing lithium salt, and an additive, but the present invention is not limited thereto. According to actual design requirements, in other embodiments, the electrolyte may also optionally include other components.
[0038] In some embodiments, the organic solvent is selected from a combination of an ester solvent and an ether solvent, and the volume ratio of the ester solvent to the ether solvent is between 3:1 and 1:1 to further improve the electroplating quality, but the present invention is not limited thereto.
[0039] In some embodiments, the organic solvent may be composed of ethylene carbonate (EC), diethyl carbonate (DEC), 1,3-dioxolane (DOL), mixed ethylene glycol dimethyl ether (DME), and acetaldehyde diethyl acetal (DEE), but the present invention is not limited thereto.
[0040] In addition, since excessive high-activity lithium metal and the electrolyte in the lithium battery will undergo continuous and irreversible reactions, an excessive SEI layer will be formed at the interface between the electrolyte and the lithium metal electrode, causing the effective active lithium to be continuously consumed, resulting in low coulombic efficiency. In addition, during long-term lithium battery operation, such as plating / stripping, the effective active lithium is stripped from the current collector and coated by the SEI layer, which can easily cause the active lithium to fail, known as the dead lithium phenomenon. The above-mentioned electrolyte design of the present invention can reduce the occurrence of the dead lithium phenomenon, for example, the dead lithium content is less than 25%, but the present invention is not limited to this.
[0041] It should be noted that the electrolyte in the subsequently assembled lithium battery can also be designed similarly to the electrolyte of the present invention, so as to have a wide potential window, good lithium ion conductivity (e.g., greater than 10 -4 S / cm), high lithium ion conductivity, non-conductive electrons (less than 10 -10 S / cm), and has both chemical stability and battery compatibility, but the present invention is not limited thereto.
[0042] In addition, through the design of the aforementioned electrolyte, the negative electrode of the lithium battery of the present invention can effectively retain the high energy density of lithium metal, improve the problems of lithium excess and poor lithium plating / stripping efficiency of the negative electrode copper current collector in the anode-free battery, but the present invention is not limited to this.
[0043] The following experimental data are listed to illustrate the effects of the present invention, but the scope of the present invention is not limited to the scope of the embodiments.
[0044] Example 1: It is composed of 1M LiTFSI (EC:DEE=1:1), 1wt% LiNO3 and 0.5wt% FEC, wherein 1MLiTFSI (EC:DEE=1:1) represents that 1 liter of electrolyte contains 1 mol of LiTFSI, and 1 liter of electrolyte is composed of EC and DEE in a ratio of 1:1, and wt% is relative to the total weight of the electrolyte. Similar expressions have similar definitions and are not repeated here.
[0045] Example 2: composed of 1M LiTFSI (EC:DEE=1:1), 2wt% LiNO3 and 0.5wt% FEC.
[0046] Example 3: composed of 1M LiTFSI (EC:DEE=1:1), 1wt% dimethyl sulfoxide (DMSO), 3wt% LiNO3 and 0.5wt% FEC.
[0047] Example 4: composed of 1M LiTFSI (EC:DME=1:1), 1wt% LiNO3 and 0.5wt% FEC.
[0048] Example 5: composed of 1M LiTFSI (EC:DME=1:1), 2wt% LiNO3 and 0.5wt% FEC.
[0049] Example 6: composed of 1M LiTFSI (EC:DME=1:1), 3wt% LiNO3 and 0.5wt% FEC.
[0050] Comparative Example 1: 1M LiPF6 (EC:DEC=1:1).
[0051] Comparative Example 2: composed of 1M LiTFSI (DOL:DME=1:1), 1wt% LiNO3.
[0052] The formulations shown in Examples 1-6 and Comparative Examples 1-2 were used as electrolytes, CR2032 button-type battery components were used to assemble lithium-copper half-cells, and lithium was used as the lithium source for electroplating. 2 , electroplating for 1 hour (1mAh / cm 2 ), the lithium deposition layer thickness is about 5 microns (um), and the plated lithium copper composite foil (lithium battery negative electrode) is taken out.
[0053] The data in Table 1 are for testing the lithium-copper half-cell assembled with the above-mentioned lithium-copper composite foil, using a PP / PE / PP three-layer isolation membrane, and the battery electrolyte is composed of 1M LiTFSI (EC:DME=1:1), 5wt% LiNO3 and 0.5wt% FEC, and the coulombic efficiency is tested at different current densities.
[0054] By comparing the results of the embodiment and the comparative example in Table 1, the following conclusions can be drawn: the coulomb efficiency of the lithium-copper composite foil electroplated by the electrolyte of the embodiment is superior to that of the electrolyte of the comparative example at different current densities, which proves that the quality of the lithium layer plated by the optimized electrolyte formula of the present invention (such as the electrolyte formula of the embodiment 1 including at least an ether additive (FEC) compared with the comparative example 2) is better than that of the electrolyte formula of the comparative example, and the lithium layer is better than that of the electrolyte formula of the comparative example at a current density greater than or equal to 2 mA / cm 2 Can have significantly superior performance.
[0055] Table 1
[0056]
[0057] according to Figures 3 to 18 Compared with the electrical results, the smoother the surface of the plated lithium layer, the better the coulombic efficiency under high current density. The SEM image of Comparative Example 1 shows obvious granular and strip-shaped lithium dendrites on the surface. Comparative Example 2 also begins to have a granular and uneven surface, so the electrical results are also not good.
[0058] In addition, the weight loss of the lithium layer is measured before and after the lithium-copper half-cell electrical performance test to determine the quality of the lithium layer. The better the quality of the lithium layer, the less lithium is lost. The lost lithium is referred to as dead lithium. The weight of lithium before electroplating is referred to as electroplated lithium weight. The higher the percentage of dead lithium, the more positively correlated it is with the electrical performance results. This method can be used to judge the quality of the plated lithium layer. From the results in Table 2 below, it can be seen that Examples 1-6 have obvious improvements in the percentage of dead lithium compared to Comparative Examples 1-2.
[0059] Table 2
[0060]
[0061]
[0062] In summary, the manufacturing method of the lithium battery negative electrode of the present invention is to form a copper-lithium composite structure through an electroplating process, and through the electrolyte design of the electroplating process, a fluorine-containing protective film can be formed on its surface. In this way, the generation of lithium dendrites can be effectively reduced during the charging and discharging of the lithium battery, and the probability of problems such as short circuit and thermal runaway can be reduced. That is, the lithium battery negative electrode manufactured by the method of the present invention can effectively improve the stability and cycle life of the assembled lithium battery.
[0063] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for manufacturing a negative electrode of a lithium battery, characterized in that: include: Provide copper foil; as well as An electroplating process is performed to form a lithium deposition layer on the copper foil, wherein the electrolyte used in the electroplating process includes an organic solvent and a fluorine-containing lithium salt, wherein the organic solvent includes an ester solvent, an ether solvent, an alcohol solvent or a combination thereof, and the fluorine-containing lithium salt includes lithium hexafluorophosphate, lithium bis(fluorosulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorooxalatoborate, lithium bis(trifluoromethanesulfonyl)imide or a combination thereof.
2. The method for manufacturing a negative electrode of a lithium battery according to claim 1, characterized in that: The electrolyte at least includes an ester solvent, the volume ratio of which is more than 50%.
3. The method for manufacturing a negative electrode of a lithium battery according to claim 1, characterized in that: The usage ratio of the fluorine-containing lithium salt in the electrolyte is between 0.1 mol / L and 5 mol / L.
4. The method for manufacturing a negative electrode of a lithium battery according to claim 1, characterized in that: The current density of the electroplating process is between 1 mA / cm 2 Up to 5mA / cm 2 between.
5. The method for manufacturing a negative electrode of a lithium battery according to claim 1, characterized in that: The thickness of the lithium deposition layer is between 1 micrometer and 20 micrometers.
6. The method for manufacturing a negative electrode of a lithium battery according to claim 1, characterized in that: The electrolyte further includes an additive, and the additive includes lithium nitrate.
7. The method for manufacturing a negative electrode of a lithium battery according to claim 6, characterized in that: The additive is used in the electrolyte in a proportion between 1 wt % and 10 wt %.
8. The method for manufacturing a negative electrode of a lithium battery according to claim 1, characterized in that: The organic solvent is selected from a combination of the ester solvent and the ether solvent.
9. The method for manufacturing a negative electrode of a lithium battery according to claim 8, characterized in that: The volume ratio of the ester solvent to the ether solvent is between 3:1 and 1:
1.
10. The method for manufacturing a negative electrode of a lithium battery according to claim 1, characterized in that: The surface of the lithium deposit layer includes a fluorine-containing compound.